KAJIAN APLIKASI PANTULAN SINYAL GNSS UNTUK PEMANTAUAN KETINGGIAN PERMUKAAN AIR LAUT - Buldan Muslim; Charisma Juni Kumalasari; Novie Chiuman; Muhammad Ichsan Fadhil Arafah (Komunikasi Fisika Indonesia, 2019)
Design and experiment of ocean current power generation system have been carried out using the Bach In Indonesia, the tsunami early warning system only applies the earthquake and hydrosphere relationship model to predict tsunamis. To date, no tsunami detector has used radar or GNSS technology. GNSS technology can be applied as an early warning system for tsunamis, provided that tsunamis are caused by earthquakes greater than 7 magnitudes, occur 70 kilometers below sea level, and are caused by normal faults. This could be an alternative to Bouy GNSS which is expensive to install and maintain, especially for countries with vast oceans such as Indonesia. In this paper, a review of the application of GNSS signal reflection was carried out using one International GNSS Service (IGS) station, JOG2, and one Continuously Operating Reference Station (CORS), CLSA, each located in Java and Sumatra to investigate the availability of sea level monitoring in Indonesia. Determination of sea level is obtained from two methods, the GNSS signal phase data analysis method and the GNSS Signal-to-Noise Ratio (SNR) data analysis method. Both methods use reflected GNSS signals or multipath effects to obtain sea level. The results of the study show that the number of satellites that pass through Indonesia every 15 minutes is enough to get sea-level data  every 15 minutes to one hour. This shows that it is possible to apply the multipath effect to obtain sea level information in Indonesia to detect tides and tsunamis as part of the tsunami early warning system in Indonesia.